Hemoglobin levels of infants from 0 to 6 months hospitalized in the Instituto Nacional de Salud del Niño, 2015 - Fernández-Oliva, Justa D. (2019)
Introduction. In Peru, we have few studies related to anemia that covers the first year of life. There are aspects in the way of establishing the diagnoses, treatments and interventions at the population level, which require specialized approaches and approaches that help to improve this public health problem. Objective. To determine the hemoglobin levels of infants 0 to 6 months of age hospitalized in the medicine services of the Instituto Nacional del Niño in 2015. Methods. 80 medical records of hospitalized patients were reviewed. The infants whose cause of hospitalization was not related to comorbidities and who lived at sea level were identified. Results 55% of infants presented anemia. The main reason for hospitalization was bronchiolitis (36.3%) followed by pneumonia (20%). Conclusion. 55% of infants from 0 to 6 months hospitalized presented anemia in our investigation.